A descriptive study on the magnitude and factors associated with domestic violence against pregnant women in Nsanje District, Southern Malawi - Chasweka, Robert John (2021)
Domestic violence (DV) against pregnant women exists in Malawi but its magnitude is unknown due to scanty published data on the subject. The aim of the study was to determine the extent of, and factors associated with DV against pregnant women attending antenatal clinic at Nsanje District Hospital in the Southern Region of Malawi. A descriptive quantitative study using a random sample of 292 pregnant women was conducted. A structured questionnaire was administered to each pregnant woman that consented to participate in the study. Relationships among variables were established by running a correlation matrix using SAS. Statistical significance about the association between variables was determined by Chi-square tests. The findings indicate that the majority (58.6%) of women were psychologically, physically and sexually abused during pregnancy. Positive correlations were found between DV and witnessing abuse in the home (p<0.05), smoking partners (p<0.01), family debt (p<0.01) and being ever hurt before this pregnancy (p<0.05). Associations were found between DV and male control of finances and decision making, alcohol use by partner, marital conflicts and being pregnant; but not with bride price, age, and low education status. Majority of women (40.9%) found disclosing acts of violence to uncles and parents helpful, and 63.7% suggested marriage counselling as a helpful service. Over 90% of women regarded DV as a private life issue and therefore hindered disclosure. Some of the recommendations from the study include public awareness campaigns, couple counselling, and routine antenatal screening services for DV, and Government’s commitment in implementation of laws and policies that protect the rights of women.